1996
DOI: 10.1073/pnas.93.9.4246
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase content of hypothalamic explants: increase by norepinephrine and inactivated by NO and cGMP.

Abstract: Release of luteinizing hormone (LH)-releasing hormone (LHRH), the hypothalamic peptide that controls release of LH from the adenohypophysis, is controlled by NO Since citrulline remains in the sample, whereas the equimolar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 15 publications
(10 reference statements)
2
42
1
Order By: Relevance
“…We further confirmed that we actually had increased the content of enzyme by isolating the enzyme according to the method of Bredt and Snyder (20) and then measuring the conversion of labeled arginine to citrul-line. The conversion was significantly increased by NE (19).…”
Section: Role Of No In Control Of Lhrh Releasementioning
confidence: 82%
See 2 more Smart Citations
“…We further confirmed that we actually had increased the content of enzyme by isolating the enzyme according to the method of Bredt and Snyder (20) and then measuring the conversion of labeled arginine to citrul-line. The conversion was significantly increased by NE (19).…”
Section: Role Of No In Control Of Lhrh Releasementioning
confidence: 82%
“…Furthermore, high concentrations of cGMP released by NO also acted in the explants or even in the homogenates to suppress the activation of NOS. This pathway could also be active in the presence of high concentrations of NO, such as would occur in infection by induction of inducible NOS by bacterial or viral products (19).…”
Section: Role Of No In Control Of Lhrh Releasementioning
confidence: 99%
See 1 more Smart Citation
“…The content of NOS in the tissue at the end of the experiments was estimated by the modified citrulline method (10). Because arginine is converted by NOS in the presence of O 2 and cofactors into equimolar concentrations of citrulline that remains in the tissue and NO that rapidly degrades, measurement of [ 14 C]citrulline produced from [ 14 C]arginine added to the homogenized muscle provides a convenient measure of the activity of NOS.…”
Section: Metabolism Of [ 14 C]arachidonic Acidmentioning
confidence: 99%
“…In studies not related to fever research, it has been shown that norepinephrine (NE) activates e-, n-, and iNOS in brain (1,8,21). Thus, in the case of the control of the release of luteinizing hormone-releasing hormone (LHRH) from the hypothalamus, the NE-induced increased activity of NOS has been specifically attributed to the activation of ␣ 1 -adrenoceptors (AR) on NOergic neurons (8).…”
mentioning
confidence: 99%